Pembinaan Karakter Anak melalui Pola Asuh Ayah: Upaya Mengatasi Learning Loss di Masa Pandemi Covid-19 - Wilodati Wilodati; Rika Sartika; Supriyono Supriyono; Dadi Mulyadi Nugraha; Istiqomah Putri Lushinta (Sosietas: Jurnal Pendidikan Sosiologi, 2024)
This study aims to provide an in-depth description of the development of children's character through paternal parenting as an effort to overcome the learning loss phenomenon during the Covid-19 Pandemic in the family environment of Women Workers in Kertamukti Village, Tanjungmedar District, Sumedang Regency. The method used in this study is a case study with a qualitative approach. Data was collected by means of observation, interviews, and documentation studies. Furthermore, the data analysis techniques used include data reduction, data presentation, and drawing conclusions. Test the validity of the data using Triangulation. The results of this study are: (1) The typological trend of paternal upbringing in the TKW family environment is authoritative; (2) The character values that were nurtured by the father, especially in an effort to overcome the learning loss phenomenon during the Covid-19 Pandemic, included religious values, honesty, discipline, and responsibility; (3) The different typologies of fathers' upbringing patterns produce different child character tendencies.